Adoption and sustained use of cleaner cooking fuels in rural India: a case control study protocol to understand household, network, and organizational drivers - Praveen Kumar; Amar Dhand; Rachel G. Tabak; Ross C. Brownson; Gautam N. Yadama (BMC, 2017)
Abstract Background Implementing efficient stoves and clean fuels in low and middle-income countries are critical for improving health of poor women and children and improve the environment. Cleaner biomass stoves, however, perform poorly against the World Health Organization's indoor air quality guidelines. This has shifted the focus to systematic dissemination and implementation of cleaner cooking systems such as liquefied petroleum gas (LPG) among poor communities. Even when there is some uptake of LPG by poor communities, its sustained use has been low. Concurrent use of LPG with traditional biomass cookstoves compromises reductions in household air pollution and limits health and environmental dividends. Therefore understanding key drivers of adoption and sustained implementation of clean fuels among the poor is critical. There is a significant gap, however, in the research to understand determinants and sustained exclusive use of clean fuels in rural poor communities. Methods/design Using a case control study design, this study will explore the impact of affordability, accessibility, and awareness on adoption and sustained use of LPG among rural poor communities of India. The study uses a multistage random sampling to collect primary data from 510 households. Case group or LPG adopters constitute 255 households while control group or non-LPG adopters constitute the remaining 255 households. The study will deploy sophisticated stove use monitoring sensors in each of the stoves in 100 case group households to monitor stove use and stacking behavior (using clean and traditional systems of cooking) of participants for 12 months. Moreover, this will be the first study to explore the impact of personal social networks striated by gender on LPG adoption. This study is guided by the RE-AIM (Reach, Effectiveness, Adoption, Implementation, and Maintenance) implementation science evaluation framework. Discussion Lessons from this study will feed into a larger discussion on developing a pro-poor strategy to foster uptake and sustained use of cleaner cooking systems such as LPG. Understanding the determinants of adoption and sustained use of cleaner cooking systems through the RE-AIM framework will expand our insights on implementation of cleaner cooking systems among poor communities and will advance implementation science in the clean cooking sector. A thorough study of such implementation strategies is crucial to realize multiple UN Sustainable Development Goals on global health, climate change, and energy security.